2014
DOI: 10.1371/journal.pone.0089831
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors Regulating Lung Vasculature and Immune Cell Functions Associate with Resistance to Pneumococcal Infection

Abstract: Streptococcus pneumoniae is an important human pathogen responsible for high mortality and morbidity worldwide. The susceptibility to pneumococcal infections is controlled by as yet unknown genetic factors. To elucidate these factors could help to develop new medical treatments and tools to identify those most at risk. In recent years genome wide association studies (GWAS) in mice and humans have proved successful in identification of causal genes involved in many complex diseases for example diabetes, systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 92 publications
(125 reference statements)
0
24
0
Order By: Relevance
“…After adding 5× first strand buffer and 10 mM DTT (Thermo Fisher Scientific), 200 U M-MLV (Thermo Fisher Scientific) was added and the tube was incubated for 50 min at 37˚C and 15 min at 70˚C. Real-time PCR assay was carried out using 2 μl of cDNA as the template, 10 μl of SYBR Select Master Mix (Thermo Fisher Scientific) and primers listed in S1 Table [11,37] on the ABI Prism 7000 Sequence Detection System (Thermo Fisher Scientific). Data was analyzed by 2 −ΔΔCt methods and normalized by GAPDH.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…After adding 5× first strand buffer and 10 mM DTT (Thermo Fisher Scientific), 200 U M-MLV (Thermo Fisher Scientific) was added and the tube was incubated for 50 min at 37˚C and 15 min at 70˚C. Real-time PCR assay was carried out using 2 μl of cDNA as the template, 10 μl of SYBR Select Master Mix (Thermo Fisher Scientific) and primers listed in S1 Table [11,37] on the ABI Prism 7000 Sequence Detection System (Thermo Fisher Scientific). Data was analyzed by 2 −ΔΔCt methods and normalized by GAPDH.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…SKOR2 has been reported as a candidate gene for changes in weight and BMI in male and female adolescents [38]. STAMBPL1 was reported as a candidate gene for lung vasculature and immune cell functions in 26 inbred mouse strains [39]. We observed that one SNP (BovineHD1400017459) located in RIMS2 on BTA14 was associated with MP.…”
Section: Gwas With Additive and Dominance Effectsmentioning
confidence: 67%
“…To define module driver genes we made use of the module eigengene concept, defined as the first principal component of the module expression matrix and the module membership measure, k (21,23). To provide robustness to our findings we performed weighted gene coexpression network analysis (WGCNA) on an independent publicly available lung transcriptome dataset generated from female mice (9-12 wks old) uninfected (n = 5) and 6 h after S. pneumoniae serotype 2 strain D39 intransal infection (n = 5) (GSE49533) (24).…”
Section: Differential Gene Expression Analysis and Modular Network Comentioning
confidence: 93%
“…To provide robustness to our findings we performed differential gene expression and unsupervised weighted gene coexpression network analysis using a publicly available gene expression dataset of pneumococcal lung infection in BALB/c mice (GSE49533) (24). Differential gene expression analysis between BALB/c mice discordant for pneumococ- Modular organization of the pulmonary transcriptome during pneumococcal pneumonia.…”
Section: Temporal Patterns and Regulatory Drivers Of The Host Modularmentioning
confidence: 93%
See 1 more Smart Citation